Possible Unintended Consequences of Basel III and Solvency II. (IMF Working Papers; Working Paper ;, 2011)
In today's financial system, complex financial institutions are connected through an opaque network of financial exposures. These connections contribute to financial deepening and greater savings allocation efficiency, but are also unstable channels of contagion. Basel III and Solvency II should improve the stability of these connections, but could have unintended consequences for cost of capital, funding patterns, interconnectedness, and risk migration.